"Whatever Happened to Predictability?": Fuller House, (Post)Feminism, and the Revival of Family-Friendly Viewing. (May 2018) - Loock, Kathleen
This article examines the Netflix revival of Full House, the family sitcom about three single men raising three girls that was part of the family-friendly "TGIF" (Thank Goodness It's Funny) lineup ABC aired on Friday nights in the 1980s and 1990s. The 2016 release of Fuller House, I argue, was driven not only by the possibility to exploit an existing property with ongoing media and cultural presence in times of "peak TV" but also by Netflix's strategic efforts to revive the bygone days of TGIF-style programming and reinvent family-friendly viewing in the era of complex television and online streaming platforms. In analyzing the Full House revival—its production and reception contexts, its carefully crafted text and paratexts, its position among complex dramas and edgy sitcoms—I will also trace the ways in which Fuller House engages in postfeminist discourse and raises pertinent questions about family values, gender roles, and ethnic diversity.